Taxes and Tax Systems in Sustainable Development Economics - Cieślukowski , Maciej (Studia Oeconomica Posnaniensia, 2014)
Traditional economics is being criticized because it is not able to explain the complex phenomena occurring in modern economies or propose effective solutions to global problems. Sustainable Development Economics proposes an alternative order for the global economy in the 21st century according to a new paradigm of sustainable and integrated economic, socio-cultural and ecological development. An important part of the new order is an effective tax system. Assuming a thesis that sustainable development, apart from other factors, needs sustainable taxes, this paper defines a sustainable tax and a sustainable tax system, as well as indicating the criteria for their assessment.